Evolving Validity and Reliability in Qualitative Educational Research - Victor Justice PITSOE; Ștefan VLĂDUȚESCU (Annals of the University of Craiova for Journalism, Communication and Management)
This article critically examines the concepts of validity and reliability in educational research through the lens of Denzin and Lincoln's work, particularly their 2023 SAGE Handbook of Qualitative Research. It explores four key themes